An indirect veneer technique for simple and esthetic treatment of anterior hypoplastic teeth - Amit Khatri; B Nandlal (Wolters Kluwer Medknow Publications, 2010)
This study describes a technique for treating anterior hypoplastic teeth using indirect nanocomposite veneer restoration. The prime advantage of an indirect veneer technique is that it provides an esthetic and conservative result. One of the most frequent reasons that patients seek dental care is discolored anterior teeth. Although treatment options such as removal of surface stains, bleaching, microabrasion or macroabrasion, veneering, and placement of porcelain crowns are available, conservative approach such as veneer preserves the natural tooth as much as possible. Full veneers are recommended for the restoration of localized defects or areas of intrinsic discoloration, which are caused by deeper internal stains or enamel defects. Indirectly fabricated veneers are much less sensitive compared to a operator's technique and if multiple teeth are to be veneered, indirect veneers can be usually placed much more expeditiously. Indirect veneers last much longer than the direct veneers. Therefore, indirectly fabricated veneers are more advantageous than directly fabricated veneers in many cases.